Engine tribology: enhancing energy efficiency for cleaner environment - Haji Hassan, Masjuki; M., Gulzar; M. A., Kalam; N. W. M., Zulkifli; Maleque, Md. Abdul; M. S. S., Malik; A., Arslan (CRC Press, 2023)
Ever increasing environmental legislations for greenhouse gases reduction and the trend towards energy conservation demands environmentally conformable lubrication solutions. It has been estimated that about one-third of the worldwide energy resource is being consumed to overcome frictional losses (Holmberg & Erdemir, 2017). While considering the frictional losses in a typical automotive engine, worldwide, one passenger car uses, on average, 340 liters of fuel per Engine Tribology 223 year. This would correspond to an average driving distance of 13,000 km/year (Holmberg et al., 2012). As huge numbers of reciprocating IC engines are in operation worldwide, even the small improvement in engine efficiency, emissions and reliability can have a significant effect on the global fuel economy and the environment in the long term. Concerning energy consumption within the IC engine, 48% of the energy consumption developed in an engine is due to frictional losses (Tung & McMillan, 2004). This results in millions of tons of CO2 emission per year (Braun et al., 2014). Modern tribology requires the use of low friction surfaces and improved lubrication to overcome the environmental concerns while meeting the customer requirement of fuel economy and low emissions. From an environmental point of view, low fuel economy is correlated with increased hazardous emissions (Taylor, 1998; Merlo, 2003); thus, there is need for such engine systems which have high fuel economy and lower emissions than before, and this can be accomplished by the wide use of low friction materials, coatings and high-performance lubricants (Erdemir, 2005; Johnson & Diamond, 2001; Beardsley et al., 1999).